2018
DOI: 10.7573/dic.212525
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein (HDL) functionality and its relevance to atherosclerotic cardiovascular disease

Abstract: Several prospective epidemiological studies have shown that there is a clear inverse relationship between serum high-density lipoprotein-cholesterol (HDL-C) concentrations and risk for coronary heart disease (CHD), even at low-density lipoprotein-cholesterol (LDL-C) levels below 70 mg/dL. However, more recent evidence from genetic studies and clinical research has come to challenge the long-standing notion that higher HDL-C levels are always beneficial, while lower HDL-C levels are always detrimental. Thus, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(143 citation statements)
references
References 65 publications
3
111
0
7
Order By: Relevance
“…Troponin concentration in CAD patients in the present study was within the normal range, and this disagrees with the previously reported association with increased CVD risk, which may be due small sample size or medications intake [28]. The lipid profile analysis showed only a significant association between HDL and CAD There is a clear inverse relationship between serum high-density lipoproteincholesterol (HDL-C) concentrations and the risk for coronary heart disease (CHD), even at lowdensity lipoprotein-cholesterol (LDL-C) levels below 70 mg/dL [29]. High HDL-C, reduced HDL phospholipid content, and cholesterol efflux capacity are associated with the paradoxical development of CAD [30].…”
Section: The Association Of Il-33 With Crp and Troponinmentioning
confidence: 66%
“…Troponin concentration in CAD patients in the present study was within the normal range, and this disagrees with the previously reported association with increased CVD risk, which may be due small sample size or medications intake [28]. The lipid profile analysis showed only a significant association between HDL and CAD There is a clear inverse relationship between serum high-density lipoproteincholesterol (HDL-C) concentrations and the risk for coronary heart disease (CHD), even at lowdensity lipoprotein-cholesterol (LDL-C) levels below 70 mg/dL [29]. High HDL-C, reduced HDL phospholipid content, and cholesterol efflux capacity are associated with the paradoxical development of CAD [30].…”
Section: The Association Of Il-33 With Crp and Troponinmentioning
confidence: 66%
“…HDL is synthesized in the intestine and the liver and consists of a heterogeneous group of particles, which differ in density, size, electrophoretic mobility, and apolipoprotein content [5,9] . Furthermore, the HDL particles present marked structural, physiochemical, compositional and functional heterogeneity and have significant differences in their biological properties [5,10,11] .…”
Section: Hdl Structure and Heterogeneitymentioning
confidence: 99%
“…On the other hand, there is ample clinical evidence showing that HDL functionality, more than HDL-C concentration per se, plays a crucial role in atheroprotection [5,6] . HDL functionality is assessed by the cholesterol efflux capacity (CEC), which determines the ability of HDL to accept cholesterol from macrophages for excretion into the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages cholesterol e ux as the rst critical step of RCT which is considered a key atheroprotective property [16]. The impaired HDL cholesterol e ux capacity (CEC) has been proven to increase the risk of CVD, which is independent of the plasma HDL-C levels [17,18]. However, the epidemiological data that have been performed to explore the association between CEC and RA was less convincing.…”
Section: Introductionmentioning
confidence: 99%